PERBEDAAN KUALITAS CROISSANT DENGAN PENGGUNAAN METODA MELIPAT ADONAN YANG BERBEDA - Sahputra, Edo; Elida, Elida; Fridayati, Lucy (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
This research background by the fourth method of folding the dough used in the manufacturing process Croissant, but used only one method. The purpose of this study was to analyze and compare the quality of Croissant which includes volume, shape, layer, layer neatness, color, aroma, texture, and flavor by using two different methods of folding the dough is a method of France and the Dutch. This type of research is pure experimentation (true experiment) using randomized complete design with the object of research is Croissant. The data were analyzed using a different test (T test) to see a noticeable difference between the two treatments with significance level of 1%. Different test results showed that there is no real difference in quality between the two treatments (X1 and X2) for Fhitung volume (-2.587), shape (-0.784), forms a layer (-1.414), neatness layer (-1.414), Color (-1.706), Aroma (-1.633), texture (-0.535), and taste (-0.894) <F table (3.36). Based on the test results Croissant level, the sample X2 (Dutch Method) got the highest score on each indicator of quality.Keywords: Folding Dough Method, Quality Croissant